STEEL GIRDER COMPOSITE BRIDGE STRENGTHEN SYSTEM DESIGN WITH EXTERNAL PRE-STRESSED METHOD - STEVEN ISKANDAR, MICHAEL
This thesis explained about the construction of composite bridge with steel girder based on bridge load regulation in SNI 1725:2016 and earthquake load regulation in SNI 2833:2016. As a composite with the major materials were steel and concrete, the steel design were accorded to RSNI T-03-2005 Steel Structure Design for Bridge and SNI 1729:2015 Specification for Steel Structure Building. For concrete structure, the design were created as RSNI T-12-2004 ruled. Other than that, AASHTO LRFD Bridge Design Specification was also included as additional design guideline. Initial bridge were modelled using MIDAS Civil 2011, in order to generate internal forces due to load combinations assigned. The bridge were designed in the concept of LRFD (Load Resistance Factored Design) toward structure elements and joints. After the initial bridge were analyzed, next step was rearrange the loads that caused exceed in the planned loads in SNI 1725:2016. This new loads would outpace the bridge capacity. Therefore, an additional strengthen system would be required. The strengthen system chosen was external pre-stressed. But eventually, the current regulations have not covered all about external pre-stressed on composite element yet clearly. The design then approached in some tendon layouts and resulted an appropriate strengthen bridge.